The Fourth Dimension: Development and Clinical Implementation of 4D Imaging for Real-Time Visualization of Dynamic Physiological Processes - Alahmadi, Wael Ayed; Ali Marwi Al Mokhalfi; Mohammad Abdulghani Hajomar; Mohammed Obaid Alharbi; Awadh Rashdan A Alharbi; Abdallah Rajeh Al Gohani; Nejaa Nasser Alharbi; Naif Salah Aljohani; Turki Awadhallah T Aljabri; Tawfek Awdalh Alofi (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Traditional medical imaging modalities have historically provided static, two- or three-dimensional anatomical snapshots, limiting comprehension of inherently dynamic physiological processes. The evolution toward four-dimensional (4D) imaging—incorporating the temporal dimension—represents a paradigm shift in diagnostic medicine, enabling visualization of dynamic phenomena in real-time. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This narrative review comprehensively examines the development, technical foundations, and expanding clinical implementation of 4D imaging techniques across major modalities, focusing on their role in capturing and quantifying physiological dynamics. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A systematic literature search of PubMed, IEEE Xplore, and Scopus databases (2015-2025) was conducted, with emphasis on technological innovations, validation studies, and clinical outcome research. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Significant advancements in 4D ultrasound, CT, MRI, and nuclear medicine have enabled unprecedented visualization of cardiac motion, respiratory dynamics, blood flow patterns, and metabolic processes. Key applications include fetal cardiac assessment, functional neuroimaging, radiotherapy planning, and intraoperative guidance. Despite transformative potential, challenges persist in data management, standardization, and clinical integration. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> 4D imaging has matured from research curiosity to clinical reality, providing novel insights into physiological function and pathology. Successful implementation requires continued technological refinement, establishment of standardized protocols, and validation through prospective clinical trials to fully realize its potential in personalized medicine.